Pulmonary function in swimmers exposed to disinfection by-products: a narrative review - Boraczyński, Michał; Balcerek, Tomasz; Rożkiewicz, Nikola; Pabiszczak, Monika; Harasymczuk, Michał; Sławska, Aneta; Lutomski, Przemysław (Frontiers in Physiology, 2025)
Swimming produces many psychophysiological effects, including blood, hormonal, enzymatic, pulmonary, cardiovascular and energetic adaptations. However, asthma and allergies are becoming increasingly prevalent medical issues among elite endurance-trained swimmers, where exercise-induced asthma or bronchospasm is frequently reported. Heavy endurance swimming training, especially under adverse conditions, stresses the airway mucosa, leading to inflammatory changes, as observed in induced sputum in competitive swimmers. In addition, chlorine-based disinfectants (CBDs) are commonly used in indoor pools due to their effectiveness and lower relative cost. Many of these substances have carcinogenic and genotoxic properties, and exposure to DBPs have been linked to adverse respiratory effects. The association between long-term exposure to a chlorinated swimming pool and elevated serum sIgE levels suggests a link between allergens, chlorine exposure and the development of various pulmonary dysfunctions. Thus, the combination of intense and repeated physical endurance training over extended periods, along with suboptimal environmental conditions, may contribute to the development of rhinitis, asthma and bronchial hyperresponsiveness in athletes. While occasional or low-level exposure to chlorine might not be harmful, regular swimmers, especially those at competitive levels, are at a higher risk of developing respiratory disorders. Because these potential risks of exposure to CBDs must be balanced against the benefits of swimming and the risk of microbial infections in pools, we recommend better pool management and regular health checks for swimmers. Fortunately, the reduction of bronchial symptoms in swimmers who reduce training volume and intensity suggests that the negative effects on pulmonary function may be reversible. For these reasons, it is crucial to develop effective respiratory protection strategies, including medical interventions and modifications to the pool environment. Practical steps such as reducing chlorine use, ensuring proper hygiene before swimming and using swim caps can minimise risks. Research should also explore safer alternatives to CBDs, such as ozonation, and improved ventilation to reduce air pollutants.